Influence of cooling of crab (Scylla spp.) juveniles on the physiological changes and survival during storage - Geromiano, Merlyn F. (University of the Philippines Visayas, 2017)
mud crabs alson known as mangrove crabs, belong to the genus Scylla and consists of fur species, S. serrata, S. olivacea, S. tranquebarica, and S. paramamosain. Mud crabs are widely distributed throughout the Indo-West Pacific Region where they inhabit most areas of the mangrove-lined coastal habitats. One of the major constraints identified in the development of mud crab aquaculture sector is the limited supply of crab juveniles which comes primarily from wild seeds collected from mangrove areas. Crabs collected from the wild vary in size from fly size which are <5mm carapace width (CW) to matchbox size (~75mm CW). These crab seeds are transported to grow-out ponds,pens and cages where they are cultured to marketable sizes. Mortality of mud crab juveniles during handling, storage and transport is an important concern considering the limited supply and the high value of these seeds. The high mortality rate during harvest, storage and transport of crabs is brought about by stress, post-harvest handling and exposure to wind and humidity. To address the issue of high mortality in the live trade of mud crabs, various storage and transport schemes were developed to maximize the health, survival and quality of crabs such as packaging in chilled sawdust or hessian, immersion on specially designed tanks or viviers, packing of crabs in layers separated by moistened materials and maintaining of crabs in spray system to retain moisture and temperature.